Development of demand model for regional commodity flow in the Philippines - Naval, Herminio S.
Transportation planners and engineers are becoming more aware of the need for planning at the regional level. Transportation problems are no longer confined to urban areas. Emerging patterns of passenger and commodity flow movement have direct impact on the growth or decline of the regional economies. As developments in passenger and cargo handling are becoming more sophisticated so are the problems associated with it. Thus, a basic understanding on the relationship between economic activity, investment and goods movement is needed. The research is concerned with the development of demand models for regional commodity flow. It analyzed past and present patterns of commodity movement using measures of regional economic activities as well as infrastructure investments as explanatory variables. IT also described qualitatively and quantitatively the patterns of goods production, consumption and shipment among the regions of the country. It also assessed the suitability of using standard techniques in modelling goods movement. The study used data taken from the National Statistics office and from several government agencies dealing with regional transportation planning. The study revealed how airport investments, gross value added in services, mining and quarrying, gross value added in construction plus the presence of seaports relate to goods production, consumption and distribution. It was also shown that trade imbalance exists in most of the regions and that majority of domestic trading occurs between the more developed regions of the country. It found out how traditional methods of demand modelling fail when faced with goods movement. As such, the study recommended that further studies, research, and more refined approaches to freight modelling be undertaken.